Comparative study of the performances during match play of an elite-level spin bowler and an elite-level pace bowler in cricket - Justham, L. M.; Cork, A. E. J.; West, A. A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
Previous experimental studies into the dynamics of a ball-racket impact have recorded ball velocities and trajectories in one or two dimensions. These studies were limited in terms of possible impact positions and the ability to represent realistic impact conditions. As the number of dimensions in an experiment increases, it becomes difficult to isolate single variables and to monitor their effect on the output. This paper describes a method of accurately assessing the effect of specific independent variables in impact experiments with a large number of variables. A total of 900 impacts on a Head Ti-S6 tennis racket were recorded within bespoke impact apparatus. The impact velocity, the impact angle, the impact position, and a restrictive torque about the handle were varied between each impact. Each test was recorded with two Phantom high-speed video cameras at 600 frames/s; the use of two cameras allowed the ball trajectory to be tracked in three dimensions. A multi-variate fit based on a second-order polynomial was used to establish trends within the data. It was found that applying a torque about the handle reduced the angular deviation for all impact positions along the racket's transverse axis. In a standard forehand shot, a firm grip reduces the flight time and angle of trajectory of the ball after impact, suggesting that a firm grip is beneficial during competitive play.